PEMILU YANG BERINTEGRITAS DALAM NEGARA HUKUM DEMOKRATIS - Helen, Zennis (LPPM Universitas Ekasakti Padang, 2019)
The journal entitled Elections with Integrity in the State of Democratic Law was made for several reasons. First, elections are a means of implementing popular sovereignty as the implementation of normative provisions of the 1945 Constitution of the Republic of Indonesia, especially Article 1 Paragraph (2) which states that